(untitled) (European Journal of Pure and Applied Mathematics, 2018)
By Geometric element transformation method (GETMe) always we get a new element. In this paper, we investigate the regularization of heptahedra using GETMe. Energy function is a cost function for heptahedra which is also applicable for octahedra, decahedra, hexahedra etc. is defined by a particular process, which we call base diagonal apex method (BDAMe). We also try to find the characterization of different cost function using BDAMe when we transform a heptahedra by GETMe.